Performance Comparison between Two Electrodes and Three Electrodes MEMS Capacitive Switch using Architect Coventorware - Ramli, Norhaslinawati; Sidek, Othman (International Journal of Integrated Engineering, 2014)
This paper presents the electromechanical and RF performance comparison between two electrodes and three electrodes MEMS capacitive switch using Architect Coventorware. The important of this study is to react to the industries in providing low actuation voltage MEMS capacitive switches with low loss and high isolation and make it possible to be integrated with CMOS circuit. MEMS capacitive switches with three different support structure namely fixed-fixed beam, single meander and double meander have been designed and simulated in both standard and proposed structure. A standard switch consists of two parallel electrodes and a proposed switch consists of three parallel electrodes. Designing using schematic capture begin by selecting the suitable component from electromechanical library to represent membrane, support structure, anchor, bottom electrode, top electrode, ground, transmission line-in and transmission line-out. The schematic diagram has been simulated and translated to 2D layout and 3D model for physical verification. The electromechanical analysis has been carried out using DC Transfer Analysis. In DC Transfer Analysis, the value of pull-in voltage, up-state and down-state capacitance can be attained. In Small Signal Frequency Analysis the value of resonant frequency is obtained. The measurement of RF performance was done using RF Electrical Analysis. Simulation result shows the pull-in voltage for all proposed design has been reduced 40%-50% as compared to their standard counterpart. While the result for other performance including capacitances for three electrodes switch has almost same value as two electrodes structure. The switch indicates low insertion loss (-26dB) in the down-state position. This concludes that the additional top membrane does maintain the good electromechanical and RF performance of MEMS capacitive switch.